Use of green fluorescent protein as molecular marker for tagging Bacillus brevis in soil under the control of a novel constitutive promoter F1 - Chen, Yunpeng; Shen, Daleng; Yang, Mingjie (Folia microbiologica, 2005)
A constitutive expression vector pHY300-Flgfp was constructed to test the function of promoter F1 subcloned from a rice epiphyte Bacillus brevis strain DX01. The DX01 cells harboring plasmid pHY300-F1gfp were detected to produce bright green fluorescence. Subsequently, the gfp-tagged B. brevis strain was released into the soil and its survival was investigated by PCR and the detection of green fluorescence. The spatial location of in situ gfp-tagged bacterial cells on the root surface of rice seedlings was visualized. All these results indicated that green fluorescent protein is an ideal molecular marker for the detection of the activities of promoter F1, and it is also a reliable probe to monitor specific B. brevis bacteria in the environment.
Keywords: exprese genu; DNA bakterií; Promoter Regions, Genetic; genetické vektory; zelené fluorescenční proteiny; Gene Expression; rýže (rod); semenáček; Green Fluorescent Proteins; plazmidy; reportérové geny; Fluorescence; barvení a značení; DNA, Bacterial; Oryza; kořeny rostlin; Seedlings; Genes, Reporter; půdní mikrobiologie; polymerázová řetězová reakce; Polymerase Chain Reaction; Bacillus; Genetic Vectors; fluorescence; Plant Roots; Plasmids; promotorové oblasti (genetika); Staining and Labeling; Soil Microbiology